If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 4 + 36 = 6n + -4 Combine like terms: -8 + 4 = -4 -4 + 36 = 6n + -4 Combine like terms: -4 + 36 = 32 32 = 6n + -4 Reorder the terms: 32 = -4 + 6n Solving 32 = -4 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 32 + -6n = -4 + 6n + -6n Combine like terms: 6n + -6n = 0 32 + -6n = -4 + 0 32 + -6n = -4 Add '-32' to each side of the equation. 32 + -32 + -6n = -4 + -32 Combine like terms: 32 + -32 = 0 0 + -6n = -4 + -32 -6n = -4 + -32 Combine like terms: -4 + -32 = -36 -6n = -36 Divide each side by '-6'. n = 6 Simplifying n = 6
| 5-7x=53-35x | | 15,8x+7,8-8,4x=30 | | 7-3b=-11 | | -17x-3x=13-9x | | 2x+38=10x-75 | | 6x=2x+3x+42 | | 4,2x-2,6=3,2+1,3x | | 3.50*4= | | 5x+56=9x+14 | | 4(x+25)=3(7+x) | | 1043+72x=4x+2131 | | 113-21x=x+x-186 | | x=2x+3x+42 | | 1+3x/2+2-x/3=5/6 | | 9(4g+5)= | | x=1,2x+1,3x+7 | | 245-17x=9+63 | | 4n-(7)=10 | | 18+18x-90=103-7x | | 28=74x | | 5(y+6)-8y=39 | | -2(x-2)(x+3)=0 | | .3x+1.7=.2x-.4(5x+1) | | 5c/3c-1 | | 2x+6/x-9=0 | | 8x^2-38x-10=0 | | .3(x-2)+.4x=.2(x-6) | | 2(x-4)=5/6(x+6)-6 | | 3x-23=97-9x | | 1/5(y+2)=1/10y+3/5 | | 2x-4+7=-6x+41 | | 3x-2(x-4)=8-2x+15 |